Agenesis of Maxillary Lateral Incisors: Treatment Involves Much More Than Just Canine Guidance - Silveira, Giordani Santos (Open Dent J, 2016)
OBJECTIVE: In this study, we aimed highlight some clinical features present in patients whose maxillary lateral incisors are missing, and proposed more logical, rational and predictable solutions to inform decision making in rehabilitation procedures. METHODS: Literature review and discussion. CONCLUSION: Choosing the best possible treatment for congenital absence of maxillary lateral incisors depends on the multidisciplinary diagnosis of facial, occlusal, functional and periodontal features. It also depends on the individual long-term stability, and it does not only rely on canine-guided disocclusion.